Long-term impact of different triple antihypertensive drug treatments on blood pressure control, metabolic pattern and incident events: data from the Brisighella Heart Study. (11th May 2022) - Cicero, A; Fogacci, F; Rizzoli, E; D'addato, S; Borghi, C
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): University of Bologna Purpose: The aim of this study was to comparatively evaluate clinical, laboratory and hemodynamic effects on the long term of different triple combination antihypertensive medications in a well-characterized population cohort. Methods: We considered data of a subset of Brisighella Heart Study (BHS) participants who were consecutively evaluated in three epidemiological surveys between 2008 and 2020. For the current analysis, we excluded normotensive subjects, patients treated with <3 or ≥3 high blood pressure (BP) medications without taking angiotensin-converting enzyme (ACE) inhibitors, angiotensin II receptor blockers (ARBs), calcium-channel blockers (CCB) and/or thiazide/thiazide-like diuretics. The remaining participants were divided into three groups depending on whether they were treated with ACE-inhibitors/CCBs/Thiazide, ARBs/CCBs/Thiazide or Perindopril/Amlodipine/Indapamide, either with separate drugs or fixed pill combinations. A further group of age- and sex-matched volunteers was selected as control and included patients receiving other antihypertensive medications. The long term effects of the different antihypertensive medications were compared among the pre-defined groups. Results: On the long-term, combination treatment with renin-angiotensin system (RAS) modulators, CCBs and thiazide/thiazide-like diuretics was associated with better control of diastolic BP and lipid pattern than other triple combination antihypertensive medication. Patients treated with Perindopril/Amlodipine/Indapamide did not experience any age-related increase in serum levels of total cholesterol. Moreover, during the follow-up they neither developed type 2 diabetes nor had a need for a greater number of antihypertensive drugs to improve BP control. Conclusion: Based on our observations, combination treatment with RAS modulators, amlodipine and thiazides/thiazide-like diuretics is more effective than other combination antihypertensive medications for lowering the diastolic BP and has a better impact on serum lipids. Perindopril/amlodipine/indapamide is associated with better lipids' profile than any other considered combination antihypertensive medication.